Análise do internato de medicina em clínica cirúrgica pelo discente - Silva, Agenor Antônio Barros da (2018)
The relationships of teaching and learning are so old, not restricted to the classroom, nor is the university the only place where education happens. The student is faced with difficulties, mainly regarding the distance from what is discussed in the university and how he will be able to act in his professional life. In order to minimize such difficulties it is necessary to approach these students, with the professional field where they will act. The present study had the following objectives: to analyze the Internship of Medicine in Surgical Clinic in the different practice scenarios, to identify the contributions of the practice scenarios for the medical training in the area of Surgical Clinic and to verify the applicability of the knowledge acquired in this stage. Quantitative study, developed in the medical course of IES, federal public, in the northeast of Brazil. A closed questionnaire was used with identification of the profile of the students and three scales of evaluation of the stages, after semantic adaptations: Strategies of Application of the Learning (EEAA), Strategy of Learning (EEA) and Reaction to the Course (ERC). The students mentioned that they believe that it is possible to apply what they have learned in practice, identify situations that can make application difficult, admire people who apply what they have learned, assess how they are applying what they have learned, consult the theoretical framework, literature, socialize experiences among colleagues. In the scale that deals with the control of emotion, the students did not remain calm about the possibility of making mistakes, of earning less than expected income. There is no clarity of the workload, adequacy of theoretical content and does not receive didactic material.The practical workload, the facilities of the scenarios are adequate and of quality, recognize what skills are developed. The reflections point to the need to invest in pedagogical capacities, to build with the students the planning, previous activity in a simulated environment, to maintain a fast and effective communication channel between course coordination and students. Maintain partnerships with hospital services that prioritize the quality of care, with ongoing dialogue between the IES administrative management and the hospitals agreed. To stimulate student autonomy as to their performances in the fields of stage and in the construction of their learning. The benefit of this reflection regarding the curricular internship in surgical clinics will provide extended experiences in work scenarios, better adaptation of students to realities, development of a critical sense regarding professional performance and the acquisition of professionalself-confidence.The results pointed out as a product, the proposal presented to the College of the Course to institutionalize the implementation of an instrument for the evaluation of medical internship, within the scope of FAMED/UFAL, the draft resolution proposed for this purpose was approved unanimously,according to the Minutes of the meeting.